Socioenvironmental Pathways to Conservation of Natural Resources & Environmental Betterment - Squires, Victor; Feng, Haiying (Advances in Social Sciences Research Journal, 2022)
This is an analysis of past and on-going ‘land and people’ management issues in China’s extensive rural areas. Both authors draw on more than 20 years’ experience derived from working in China’s arid northwest and on the ‘roof of the world” on the Qinghai-Tibetan Plateau (QTP). Worldwide, communities of people have adapted to hot and dry, cold and arid and hot and humid environments. They have shown their adaptability and have made remarkable innovations that enabled them to survive for centuries. But many of the strategies used now, and those unaltered from the past, are inadequate to cope with the fast-changing situation in modern China. The paper is in several parts. We explain some of the terminology around socioenvironmental thinking and its application to the real world with examples from the Qinghai-Tibetan Plateau – a vast upland in NW China. An attempt is made to show how a better understanding of the interplay of fast and slow variables can help to ensure conservation (wise use) of natural resources and serve the needs of the land users (mainly semi-nomadic herders of yaks, goats, sheep, camels and horses). We suggest that the term ‘situation betterment’ is a more realistic goal and the ‘solving’ the manifold problems (ecological, legal, economic, political and logistic) that beset land users, administrators, policy makers and the law makers. An explanation of the systems approach and its relevance to socio-environmentalism is offered